Severe and enduring prostate cancer burden attributable to smoking among old men amid global decline and socioeconomic disparities - Hao Chen; Chen Sang; Jia Jia; Shan Zheng; Minzhen Wang (Scientific Reports)
Abstract Prostate cancer (PC) is a significant global health concern, particularly among older men (OM), and smoking is a well-established modifiable risk factor contributing to its incidence and mortality. However, a comprehensive assessment of the global burden of PC attributable to smoking among OM, with specific analyses by age and Socio-demographic Index (SDI) regions, is still lacking. This study utilized data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 to systematically analyze the global burden of PC attributable to smoking among OM (aged 55 years and older) from 1990 to 2021. The analysis included trends in deaths and Disability-Adjusted Life Years (DALYs) across different age groups and SDI regions. The estimated annual percentage change (EAPC) and Joinpoint regression analysis were employed to assess temporal trends. From 1990 to 2021, the global burden of PC attributable to smoking among OM exhibited a significant decline, with the age-standardized death rate decreasing from 3.08 per 100,000 in 1990 to 1.80 per 100,000 in 2021 (EAPC: -2.02, 95% CI: -2.14 to -1.90). Similarly, the age-standardized DALY rate decreased from 65.28 per 100,000 in 1990 to 37.75 per 100,000 in 2021 (EAPC: -2.05, 95% CI: -2.16 to -1.94). However, disparities across SDI regions were evident. The high SDI region experienced the most substantial decline in burden. In contrast, the low-middle SDI region showed an increasing trend, highlighting enduring socioeconomic disparities. Notably, Despite the overall reduction in the global burden, the burden among the older age group, specifically 90–95 years old, remained the most severe in 2021. This study reveals a complex landscape of the global burden of PC attributable to smoking among OM, with an overall decline masking enduring socioeconomic disparities and a severe burden among the older age group. These findings underscore the need for targeted interventions and public health strategies to address these disparities. Future efforts should focus on implementing smoking cessation programs and improving healthcare access in vulnerable populations.